Negative hermeneutics and the notion of literary science - Serra Lopes, Francisco (Primerjalna književnost, 2007)
The meaning of negativity within the context of interpretative practices is likely to unfold, thus manifesting different or even divergent heuristic strategies. However, these have been equivocally referred to as negative hermeneutics, an expression that occurs in the discourse of authors such as Ricoeur and Jameson. The "negative", either challenging or complementing "positive" hermeneutics, has consequences for the thought of "literary science", if there is such a thing and such a possibility.
Keywords: literarna veda; literary science; literarna interpretacija; hermenevtika